Millennials in the Gig Economy: Digital Precarity, Labor Performance, and Transnational Mercenary Implications - Tubagus Fadillah; Corry Yohana; Widya Parimita (International Journal Of Economics Social And Technology, 2026)
his study examines how algorithmically managed platform work produces digital labor precarity among Indonesian millennials and identifies the structural conditions through which prolonged insecurity may increase exposure to transnational high-risk labor. Rather than assuming a direct transition from gig work to mercenary activity, the study proposes the Precariat–Transnational Risk Pathway as a cautious analytical framework linking platform control, income instability, weakened social protection, human-capital stagnation, and risky labor-mobility choices. An integrative qualitative literature review was conducted using peer-reviewed studies, Indonesian labor and legal scholarship, policy documents, and international humanitarian-law sources published primarily between 2021 and early 2026. Thematic synthesis generated four findings: algorithmic control produces constrained autonomy; income volatility encourages self-exploitation; limited training and career mobility erode human capital; and transnational security recruitment represents a conditional risk shaped by poverty, marginalization, prior skills, recruitment networks, and weak state protection. The study contributes an interdisciplinary model connecting digital labor studies with human-security analysis and recommends transparent platform governance, portable social protection, accessible grievance mechanisms, continuous reskilling, and preventive labor-migration oversight.